Tuning the electronic structure of single-walled carbon nanotube by high-pressure H2 exposure. (7th December 2018) - Kang, Hojin; Hong, Sung Ju; Park, Min; Jang, Hyun-Seok; Nam, Kiin; Choi, Soobong; Kim, Byung Hoon; Park, Yung Woo
Abstract: We report on an electronic structure change of single-walled carbon nanotube (SWNT) on hexagonal boron nitride due to electron doping via high-pressure H2 exposure. The fractional coverage of hydrogenated carbon atom is estimated to be at least θ  = 0.163 from the in situ I ds – V g measurements of the release process. Raman spectroscopy and x-ray photoelectron spectroscopy were carried out to support the in situ electrical measurements. In particular, we used the dissociative Langmuir-type model to yield the desorption coefficient k des by fitting it to the in situ electrical data. Finally, we applied this hydrogenation method to the SWNT network on the commercial Si/SiO2 substrate to open the possibility of the scalable n -type semiconducting SWNT FETs.